Exploring the effects of cognitive destination image attributes on tourist satisfaction and destination loyalty: a case study of Málaga, Spain - Vanesa F. Guzman-Parra; José Roberto Vila-Oblitas; Francisco Javier Maqueda-Lafuente (Tourism & Management Studies)
This article has attempted to provide empirical evidence of the relationships between two groups of perceived destination image attributes, tourist satisfaction and tourist loyalty. In order to explore these relationships, two groups of destination image attributes perceived in situ have been studied: “hard ware” and “human ware” attributes of a south Spain destination. A theoretical model is tested on a sample of tourists using structural equations modeling. A positive relationship is detected between the variables. From a practical point of view, recommendations were made on the importance of destination image attributes such us “hard ware attributes” and “human ware attributes” that generate favorable word-of-mouth recommendations and revisit intentions.